CONCEPTUALIZATION OF THE JOURNALISM CULTURE AND JOURNALISTS ROLLS IN COMPARATIVE PERSPECTIVE - Prodanović, Dragana M (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2020)
Within the rapidly evolving field of comparative communication studies, the social functions of journalism and the role of journalists in contemporary societies are also studied. The paper offers an overview of initial research that described only media systems without including the position and role of the actors of these systems. This broader framework later served as a starting point for a new kind of presentation of a set of ideas and practices by which journalists, consciously and unconsciously, legitimize their role in society and conceive of their work in the form of the concept of journalistic culture (Hanitzsch, 2007: 369). Empirical research on journalistic culture is focused on the actors of the journalistic process and has resulted in the insights into how the journalists perceive their own and social roles of their colleagues and how they value them. In recent years a new type of research has emerged – parallel research on the perception of journalistic roles of journalists and of the audience. Particular attention in this paper is paid to the interpretation of journalistic roles as discursively constituted structures of meaning that establish the parameters of what is desirable in a given institutional context. The aim of such research is to conceptualize the journalistic identity and its place in society.
Keywords: media systems; journalistic culture; journalistic roles; professional ideologies; social functions of journalism